Kelvin-Helmholtz Vortices as an Interplay of Magnetosphere-Ionosphere Coupling - Hwang, K.-J.; Weygand, J. M.; Sibeck, D. G.; Burch, J. L.; Goldstein, M. L.; Escoubet, C. P.; Choi, E.; Dokgo, K.; Giles, B. L.; Pollock, C. J.; Gershman, D. J.; Russell, C. T.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
The solar wind-magnetosphere interaction drives diverse physical processes on the flanks of Earth’s magnetopause, and in turn these processes couple to the ionosphere. We investigate simultaneous multipoint in-situ spacecraft and ground-based measurements to determine the role of Kelvin-Helmholtz waves at the Earth’s magnetopause and the low-latitude boundary layer in the magnetosphere-ionosphere coupling process. Nonlinear Kelvin-Helmholtz waves develop into flow vortices that twist and/or shear flux tube magnetic fields, thereby generating localized field-aligned currents. Kelvin-Helmholtz vortices on the dusk (dawn) flanks of the magnetosphere generate clockwise (counter-clockwise) rotations and upward (downward) field-aligned currents inside the flux tubes, consistent with the region-1 field-aligned current. We present in-situ MMS and Cluster spacecraft observations of Kelvin-Helmholtz vortices at the magnetopause that map to the poleward edge of the auroral regions. The FAST spacecraft and the ground-based magnetometers from which spherical elementary currents (acting as a proxy for vertical currents) can be calculated observe corresponding field-aligned current signatures. This study demonstrates the role played by the Kelvin-Helmholtz waves in linking magnetopause boundary fluctuations to ionospheric phenomena.